Advocacy leadership [ toward a post-reform agenda in education - Anderson, Gary L. , 1948- (Critical social thought series, 2009)
Lays out a post-reform agenda that moves beyond the neo-liberal, competition framework to define a accountability, a pedagogy, and a leadership role definition. This book argues for the need to move